Selective serotonin reuptake inhibitors and lung function in the multi-ethnic study of atherosclerosis lung study. (May 2022) - Armstrong, Hilary F.; Lederer, David; Lovasi, Gina S.; Hiura, Grant; Ventetuolo, Corey E.; Barr, RGraham
Abstract: Objective: Depression in patients with Chronic Obstructive Pulmonary Disease (COPD) has been shown to be chronic and potentially increase the burden of symptoms. Selective serotonin reuptake inhibitors (SSRIs) have anti-inflammatory and serotonergic effects that may improve lung function. We hypothesized that participants taking SSRIs have better lung function than those not taking SSRIs. The dataset was the Multi-Ethnic Study of Atherosclerosis (MESA) Lung Study. Use of SSRIs was assessed by medication inventory; spirometry was conducted following standard guidelines; dyspnea ratings were self-reported. Results: Contrary to our hypothesis, FEV1 was lower, and odds of dyspnea were higher among participants taking SSRIs as compared with those not taking an antidepressant; these differences persisted even with control for potential confounders including depressive symptoms. We found no evidence of a beneficial association between SSRI use and lung function or dyspnea in a large US-based cohort. Highlights: Using the MESA dataset, we analyzed if SSRIs are associated with improved lung function. There was no association with SSRIs and lung function. This investigation was among the first to assess the impact of SSRIs on lung function using epidemiologic methods.